THE RELEVANCE OF ARABIC IN ISLAMIC STUDIES: LINGUISTIC IMPLICATIONS FOR UNDERSTANDING THE QUR’AN AND HADITH - Sapitri, Dea; Khatimah, Isro; Risnawati, Reni; Geby Febiola, Wenisa (Program Studi Pendidikan Bahasa Arab, 2025)
The Arabic language plays a fundamental role in understanding the primary sources of Islamic teachings, namely the Qur'an and Hadith. As the language of revelation, the complex linguistic structure of Arabic requires deep comprehension to ensure accurate interpretation of Islamic texts. This study aims to analyze the extent to which proficiency in Arabic contributes to the understanding of Islamic texts and the impact of linguistic limitations on the comprehension of Islamic teachings. This research employs a literature review method with a descriptive-analytical approach to examine various relevant references. The findings indicate that Arabic language skills, such as grammar, morphology, and semantics play a crucial role in comprehending the contextual meanings of texts. Inaccuracies in understanding linguistic structures can lead to misinterpretations of Qur'anic verses and Hadith. Therefore, effective, innovative, and sustainable Arabic language learning strategies are necessary to enhance the quality of understanding Islamic teachings. The integration of technology in Arabic language learning also serves as a solution to expand access and accelerate the comprehension process. Thus, strengthening Arabic literacy becomes a strategic step in fostering a comprehensive, moderate, and contextually relevant understanding of Islam